A quantitative and qualitative analysis of patient group narratives suggests common biopsychosocial red flags of undiagnosed rare disease - Mariam Al-Attar; Sondra Butterworth; Lucy McKay (Orphanet Journal of Rare Diseases, 2024)
Abstract Background The ‘diagnostic odyssey’ is a common challenge faced by patients living with rare diseases and poses a significant burden for patients, their families and carers, and the healthcare system. The diagnosis of rare diseases in clinical settings is challenging, with patients typically experiencing a multitude of unnecessary tests and procedures. To improve diagnosis of rare disease, clinicians require evidence-based guidance on when their patient may be presenting with a rare disease. This study aims to identify common experiences amongst patients with rare diseases, to inform a series of ‘red flags’ that can aid diagnosis of rare diseases in non-specialist settings. A questionnaire was developed by Medics for Rare Diseases, informed by the experiences of clinicians, rare disease patients and patient advocates, and was shared with UK-based rare disease patient groups. Study participants were engaged via social media platforms, blogs and email newsletters of three umbrella rare disease organisations. The questionnaire, comprising 22 questions, was designed to identify typical experiences relating to physical and psychosocial manifestations and presentation of disease, patient interactions with healthcare providers, and family history. Results Questionnaire responses were received from 79 different rare disease patient groups and the common experiences identified were used to inform seven red flags of rare disease: multi-system involvement (3 or more); genetic inheritance pattern; continued presentation throughout childhood and adulthood; difficulties at school, especially relating to absences, difficulty participating in physical education and experiences of bullying or social isolation; multiple specialist referrals; extended period with unexplained symptoms; and misdiagnosis. In light of the red flags identified, recommendations for primary care and education settings have been proposed, focusing on the need for holistic assessment and awareness of both physical and psychosocial factors. Conclusions This study identified key commonalities experienced by patients with rare disease across physical and psychosocial domains, in addition to understanding patients’ history and experiences with healthcare providers. These findings could be used to develop a clinical decision‑making tool to support non-specialist practitioners to consider when their patient may have an undiagnosed rare condition, which may minimise the challenges of the ‘diagnostic odyssey’ and improve the patient experience.